Formation Of The Organizational Model For The Implementation Of Low-Rise Housing Investment Project And Evaluation Of Interaction Effectiveness Of Its Actors; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Minaev N. N. Nikolay Nikolaevich; Sharf I. V. Irina Valerievna; Filyushina K. E. Kristina Eduardovna; Gusakova N. V. Nataljya Vasiljevna; Dobrynina O. I. Olga Igorevna; Zharova E. A. Ekaterina Aleksandrovna; Merkuljeva Y. A. Yuliya Aleksandrovna; Dmitrieva N. V. Nataljya Valerjyanovna (2016, 2016)
Title screen